1996
DOI: 10.1590/s0034-89101996000600006
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de medicamentos por crianças atendidas em creches

Abstract: ResumoPara identificar o padrão de utilização de medicamentos em crianças, foram acompanhadas 1.382 crianças matriculadas em 15 creches municipais de São Paulo (SP)(Brasil), durante 2 meses; 512 crianças (37%) utilizaram 1.409 medicamentos (média de 50,9 medicamentos/100 crianças/ mês). Mais de 80% das crianças menores de dois anos utilizaram um ou mais medicamentos, enquanto nas outras idades esse consumo foi sempre inferior a 45%. Os fármacos mais utilizados foram os antiinfecciosos, medicamentos com ação no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
17

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
1
14
1
17
Order By: Relevance
“…[7][8][9][10][11]13,25 The lower frequency of self-medication observed in age group < 7 years should be noted. A study carried out in Holland to analyze the consumption of pharmaceuticals in individuals < 17 years showed that the prevalence of consumption is significantly higher in children < 1 year of age, followed by the 2-5 years' age group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[7][8][9][10][11]13,25 The lower frequency of self-medication observed in age group < 7 years should be noted. A study carried out in Holland to analyze the consumption of pharmaceuticals in individuals < 17 years showed that the prevalence of consumption is significantly higher in children < 1 year of age, followed by the 2-5 years' age group.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been attributed to the social roles that are traditionally reserved to mothers, including the role of promoting health in the family. 9,11,13,25 In 20.1% of the cases, advice for self-medication was given at the drugstore, a common fact in Brazil and other countries. 3,4,6,11,[19][20][21]25,27 In our study, according to the interviewees' opinion, only 1.8% of the cases of selfmedication were influenced by the media, similarly to what has been described for another medium-sized municipality in southern Brazil (2.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an increase may indicate that mothers learn and incorporate treatment practices originally recommended by a physician, but which may not always be adequate to the current situation. 6 According to a study of Australian children, selfmedication is facilitated by the availability of overthe-counter medicines, which are widely used even though there is no evidence regarding their effi cacy or information on potential risk of toxicity. 1 Over-thecounter medicines, especially those for cold and fl u symptoms, carry the risk of overdose, underdose, and adverse effects.…”
Section: Discussionmentioning
confidence: 99%